2017
DOI: 10.3233/jpd-161034
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Perceived Walking Difficulties in People with Parkinson’s Disease

Abstract: (244 out of 250)Background: While walking difficulties are common in people with Parkinson's disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 63 publications
4
33
1
1
Order By: Relevance
“…One study used both PFS and FSS with a cut‐off point of ≥ 3.3 and of > 4, respectively . The two studies using Multidimensional Fatigue Inventory (MFI) used a cut‐off point of ≥ 13 (see Revees and colleagues for cut‐off reference), and four studies adopting the Energy subscale of Nottingham Health Profile (NHP‐EN) classified as having fatigue patients who affirmed at least one of three dichotomous (Yes/No) questions (i.e., tired all the time, everything is an effort, soon out of energy; see Hagell and colleagues for cut‐off reference) . One study measured fatigue prevalence by Fatigue Questionnaire (FQ) with a cut‐off point of ≥ 4 (see Loge and colleagues for cut‐off reference), and one study measured fatigue prevalence by SEND‐PD using a cut‐off point of > 0 (see Martinez‐Martin and colleagues for cut‐off reference).…”
Section: Resultsmentioning
confidence: 99%
“…One study used both PFS and FSS with a cut‐off point of ≥ 3.3 and of > 4, respectively . The two studies using Multidimensional Fatigue Inventory (MFI) used a cut‐off point of ≥ 13 (see Revees and colleagues for cut‐off reference), and four studies adopting the Energy subscale of Nottingham Health Profile (NHP‐EN) classified as having fatigue patients who affirmed at least one of three dichotomous (Yes/No) questions (i.e., tired all the time, everything is an effort, soon out of energy; see Hagell and colleagues for cut‐off reference) . One study measured fatigue prevalence by Fatigue Questionnaire (FQ) with a cut‐off point of ≥ 4 (see Loge and colleagues for cut‐off reference), and one study measured fatigue prevalence by SEND‐PD using a cut‐off point of > 0 (see Martinez‐Martin and colleagues for cut‐off reference).…”
Section: Resultsmentioning
confidence: 99%
“…Outpatient participants were recruited from three hospitals in southern Sweden (see Figure 1, which presents a flowchart of the recruitment process). Details of recruitment and follow-up procedures have been described before, i.e., for baseline [26] and the 3year follow-up [27]. At baseline, 653 persons met the inclusion criterion of a PD diagnosis (ICD10-code G20.9), since at least one year.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…The Walk-12G is a patient-reported outcome that assesses perceived walking difficulties during everyday life, which cannot be captured by performance-based measures alone. It has previously been shown that the Walk-12G does not solely reflect walking capacity, but is largely influenced by nonmotor factors such as self-efficacy and depressive symptoms as well as self-reported freezing of gait and fatigue (Kader, Ullen, Iwarsson, Odin, & Nilsson, 2017). This is a recognized attribute of patient-reported as opposed to performance-based measures among elderly with disability, whereby patient-reported function can have stronger associations with psychosocial factors than with physical function (Bean, Olveczky, Kiely, LaRose, & Jette, 2011).…”
Section: Walk-12g Scores Correlated Significantly Withmentioning
confidence: 99%